Technical and Economic Evaluation of the Efficiency of the Application of Cross-Rod Spatial Structures in Seismic Areas - Usmon, Khushvaktov; Akram, Rakhimov; Komolboy, Isabekov (European Journal of Life Safety and Stability (2660-9630), 2022)
The article gives a technical and economic assessment of the effectiveness of the use of cross-rod spatial structures in seismic areas. The technical and economic effect of ensuring the required seismic resistance of the structure is obtained by reducing the material consumption, choosing a rational design scheme and the optimal location of the supports.